Bharat bhavishya yogi Adityanath - Paliwal, Ravikant (New Delhi Hans, 2024)
Utter Pradesh ke Mukhyamantri Yogi Adityanath ke an chuye pahluo ki charcha
Keywords: Governance Sector; Polity and Government; State Government- Yogi Aditiyanath